An Inquiry to the Working Environment Inclusivity among LQBTQ Members: A Multi-Level Mixed Design Models - Bhrendelyn B. Navales; Elizabeth R. Dumlao; Nerisa B. Abug (Garuda Prestasi Nusantara Consulting, 2023)
Social identities are significant in many facets of life since they aid in self-definition and influence how people interact with one another. Today's workforce needs more diversity and complete inclusion, despite apparent corporate backing and indications of advancement. Similarly, despite a rising commercial case for inclusiveness, the LGBTQ+ group has not seen significant advancements in the workplace. Therefore, this study aimed to ascertain whether LGBTQ employees in Cavite now work in an inclusive atmosphere. In order to investigate and comprehend the workplace acceptance of LGBTQ employees, the study used a mixed research approach. Most of the volunteers were between the ages of 25 and 34, single, recent graduates of a trade school, and served for two to three years at work. This suggested that older millennials made up the majority of the participants. The majority of participants agreed that they felt an inclusive work environment facilitated their professional development. The majority of the literature emphasizes management's dominance and commitment to advancement as key reasons why LGBTQ employees stay at their place of employment. In addition, the multilevel analysis with parallel segments for understanding the working environment among LGBTQ members serves as a framework for developing strategies for the inclusion and diversity of LGBTQ employees in the workplace. It was revealed that the inclusion of LGBTQ members in the workplace had no discernible dynamic effect on their profile. Hence, the study recommends strategies to further foster workplace inclusion. Keywords: gender, LGBT, inclusivity, social identity, workplace, mixed design